Virtual teaching of postgraduate writing: analysis about the evaluation of practices (Praxis Educativa, 2022)
Postgraduate writing teaching is an essential subject and rarely present in studies at that level.In general, students experience great difficulties in producing their final writings. Different interventions have been implemented around this difficulty, including virtual writing courses. In the present work, the results of a qualitative study of conceptual generation are reported. The study focuses on a virtual workshop aimed at promoting the writing of the thesis. The analysis of this article is focused on the teacher's evaluation about the practices. The results systematize the teaching analyzes in two dimensions: the first, about the teaching modality and the technological resources used; the second, about the didactic-pedagogical project. The constructed dimensions are essential inputs to deepen the virtual teaching practices of postgraduate writing.
Keywords: academic writing; distance education; teaching practice; classroom tecniques; educational evaluation